Using tritium to document the mean transit time and sources of water contributing to a chain-of-ponds river system: Implications for resource protection. (December 2016) - Cartwright, I.; Morgenstern, U.
Abstract: Documenting the interaction between groundwater and rivers is fundamental to understanding hydrological systems. While many studies have examined the location and magnitude of groundwater inflows to rivers, much less is known about the transit times of water in catchments and from where in the aquifer the groundwater originates. Resolving those questions is vital for protecting riverine ecosystems, assessing the impact of contamination, and understanding the potential consequences of groundwater pumping. This study uses tritium ( 3 H) to evaluate the mean transit times of water contributing to Deep Creek (southeast Australia), which is a chain-of-ponds river system. 3 H activities of river water vary between 1.47 and 2.91 TU with lower 3 H activities recorded during cease-to-flow periods when the river comprises isolated groundwater-fed pools. Regional groundwater 1–2.5 km away from Deep Creek at depths of 7.5–46.5 m has 3 H activities of between <0.02 and 0.84 TU. The variation in 3 H activities suggest that the water that inflows into Deep Creek is dominated by near-river shallow groundwater with the deeper groundwater only providing significant inflows during drier periods. If the water in the catchment can be represented by a single store with a continuum of ages, mean transit times of the river water range between <1 and 31 years whereas those of the groundwater are at least 75 years and mainly >100 years. Alternatively the variation in 3 H activities can be explained by mixing of a young near-river water component with up to 50% older groundwater. The results of this study reinforce the need to protect shallow near-river groundwater from contamination in order to safeguard riverine ecosystems and also illustrate the potential pitfalls in using regional bores to characterise the geochemistry of near-river groundwater. Highlights: We measured tritium in river water and groundwater from a groundwater-fed river. Transit times of the river water are years to decades. Transit times of regional groundwater are decades to centuries. Regional groundwater is only a minor component of the river water. Results have implications for protection of the river and its ecosystems.